Labor Market Policy In Developing Countries : A Selective Review of The Literature And Needs For The Future - Fields, Gary S., 1946- 1946- (The World Bank, 2007)
This paper presents a selective overview of the literature on modeling labor market policies in developing countries. It considers welfare economics, theoretical models, and empirical evidence to highlight the three general features needed in future research on labor market policy in developing countries. The author identifies desirable research components (welfare economics, theoretical modeling, and empirical modeling) and pitfalls in the literature (inappropriate use of productivity, reliance on wrong kinds of empirical studies, lack of cost-benefit analysis, attention to only a subset of the goods and bads, and fallacy of composition). The paper concludes with suggested topics and methods for future research. The author states that sound labor market policy requires sound labor market models. The paper makes a case for developing policy based on explicit evaluation criteria, specific theoretical models, and comprehensive empirical evidence